2021
DOI: 10.1371/journal.pone.0240284
|View full text |Cite
|
Sign up to set email alerts
|

Was facial width-to-height ratio subject to sexual selection pressures? A life course approach

Abstract: Sexual selection researchers have traditionally focused on adult sex differences; however, the schedule and pattern of sex-specific ontogeny can provide insights unobtainable from an exclusive focus on adults. Recently, it has been debated whether facial width-to-height ratio (fWHR; bi-zygomatic breadth divided by midface height) is a human secondary sexual characteristic (SSC). Here, we review current evidence, then address this debate using ontogenetic evidence, which has been under-explored in fWHR research… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 178 publications
(174 reference statements)
1
16
0
Order By: Relevance
“…There was a significant main effect of age (F 9,17587 = 88.73, p < 0.001, h 2 p ¼ 0:043, 95% confidence interval (CI) [0.037, 0.049]), with an overall tendency for FWHR to decrease with age. This result supports the previous findings of Hehman et al [20] and Hodges-Simeon et al [13], where the authors found that FWHR decreased with age. The main effect of sex was also significant (F 1,17587 = 17.05, p < 0.001, h 2 p ¼ 0:001, 95% CI [0.0003, 0.002]), with females (M = 2.19, s.d.…”
Section: Sexual Dimorphism Of Facial Width-to-height Ratio Across The...supporting
confidence: 93%
See 1 more Smart Citation
“…There was a significant main effect of age (F 9,17587 = 88.73, p < 0.001, h 2 p ¼ 0:043, 95% confidence interval (CI) [0.037, 0.049]), with an overall tendency for FWHR to decrease with age. This result supports the previous findings of Hehman et al [20] and Hodges-Simeon et al [13], where the authors found that FWHR decreased with age. The main effect of sex was also significant (F 1,17587 = 17.05, p < 0.001, h 2 p ¼ 0:001, 95% CI [0.0003, 0.002]), with females (M = 2.19, s.d.…”
Section: Sexual Dimorphism Of Facial Width-to-height Ratio Across The...supporting
confidence: 93%
“…For women, there is no clear prediction for the sizes of the FWHR across the lifespan or relationship with perceived aggressiveness as the FWHR may be a sexually selected trait in men, but not women. Studies of male and female faces showed a slow decline in FWHR from the age of 20 until the age of 40 for both men and women [ 13 ]. The authors attributed this result to the lengthening of the face with age.…”
Section: Tracking Sexual Dimorphism Of Facial Width-to-height Ratio A...mentioning
confidence: 99%
“…One of the goals of our study was to address the debates on sex-typical variation in fWHR and its’ evolutionary origin. Recently published paper by Hodges-Simeon with co-authors [ 72 ] based on data from Caucasian origin (from 3 to 40 years) and Bolivian Tsimane (from 7 to 21 years) samples of men and women tested the applicability of four variants of fWHR measurements and demonstrated that fWHR lower (including lower jaw) exhibited both adult sex differences, and the classic pattern of ontogeny for human secondary sexual characteristics (greater lower-face growth in male adolescents relative to females). In our study, we calculated six variants of fWHR (including four variants of upper fWHR, total, and lower fWHR), but none of them revealed significant sexual dimorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Classical facial indices, which are known to demonstrate certain degree of sexual dimorphism in humans, were calculated based on coordinates of facial landmarks after Procrustes superimposition. These indices included upper width-to-height ratio (upper fWHR); total width-to-height ratio (total fWHR); lower width-to-height ratio (lower fWHR); cheekbone prominence; and mandibular and nasal indices, mouth shape, mouth-face index, and height-to-width ratio of the eye [ 37 , 66 , 72 ]. The locations of the landmarks used for calculation of these indices are presented in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation